Fifteen-minute consultation: problems in the healthy child—toilet training. Issue 3 (1st March 2016) - Jacob, Hannah; Grodzinski, Ben; Fertleman, Caroline
Abstract : Toilet training is a process that all healthy children go through. It is one of the developmental milestones for which parents most often seek medical help. Despite this, many paediatricians feel unconfident managing children presenting with a toilet training problem. We address some common questions arising when assessing and managing such a child, including identifying rare but important diagnoses not to miss.